Towards inhibitors of glycosyltransferases: A novel approach to the synthesis of 3-acetamido-3-deoxy-D-psicofuranose derivatives - Bella, Maroš; Koóš, Miroslav; Lin, Chun-Hung (Beilstein Journal of Organic Chemistry, 2015)
A novel synthetic strategy leading to 3-acetamido-3-deoxy-D-psicofuranose 9 is presented. The latter compound, after some manipulations, was transformed into fully protected 3-acetamido-3-deoxy-D-psicofuranose 11 as a potential substrate for the synthesis of N-acetylglucosaminyltransferase inhibitors designed by computational methods. After the attempted thioglycosylation of 11 with EtSH in the presence of BF3·OEt2, 2-methyloxazoline derivatives 13 and 14 were isolated.
Keywords: glycosyltransferases; inhibitors; D-psicofuranose; synthesis; thioglycosylation